Logib-D und die Entgeltunterschiede zwischen Männern und Frauen in deutschen Betrieben – Eine Abschätzung des politischen Handlungsfeldes - Miriam Beblo; Clemens Ohlert; Elke Wolf (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
– Since 2009, the German Federal Ministry of Family Affairs, Senior Citizens, Women and Youth (BMFSFJ) provides a statistical tool - named Logib-D - for firms to measure their internal wage inequality voluntarily. We use our estimation model of firm-specific gender pay gaps, developed in the DFG Priority Program 1169, to simulate the wage differentials that would result from applying the Logib-D tool to all German establishments. As our analysis is based on the representative employer-employee data set of the Institute for Employment Research (LIAB) it helps to interpret the small number of results of the voluntary self-test. Our estimation results show that the majority of German establishments (81 percent in West and 64 percent in East Germany) exhibit substantial gender pay gaps which cannot be explained by differences in education or work experience. Part of the observed variance across establishments seems to be systematically linked to specific firm characteristics. We can hence identify the characteristics related to establishments exceeding or falling below a tolerated level of 5 percent gender pay gap. Our findings provide new insights into the wage structures and wage setting processes of establishments and help to identify toeholds for policy measures to reduce establishment-specific wage inequalities.
Keywords: 330; Lohnunterschied; erwerbstätige Frauen; erwerbstätige Männer; geschlechtsspezifische Faktoren; IAB-Linked-Employer-Employee-Datensatz; Lohnstruktur; Betrieb; regionaler Vergleich; sektorale Verteilung; Wirtschaftszweige; Ostdeutschland; Westdeutschland; Bundesrepublik Deutschland